Multimodal Analysis of Shifts in Gender Roles in Pakistani TV Ads - Maleeha Shahzadi; Dr. Tamsila Naeem (Dialogue Social Science Review (DSSR), 2025)
The emergence of commercials that question established gender roles in Pakistan, where they have long been common, is a significant cultural and social shift that merits this scholarly study. This qualitative study looks at how gender stereotypes are being questioned in Pakistani ads in an effort to uncover the underlying themes that point to a departure from conventional societal norms regarding gender stereotypes. This study adds to the conversation how the media may positively support gender parity in Pakistan by emphasizing the portrayal of shattering existing gender roles. The ads are selected from different PTV channels using purposive sampling approach, keeping in mind aim of the study. The selected ads are scrutinized through Multimodal Theory presented by Kress & Leeuwen in 2020. The findings reveal that advertisements represent cultural ideals, goals, and conflicts in addition to being business tools. A comprehensive and in-depth examination is made easier by the use of socio-semiotic theory, which also provides significant insights into how the media might dispel preconceptions and advance social change. The goal of this study is to add more discussion regarding media influence, female representation, and cultural development in Pakistan. This study is important because it helps us better grasp how society is changing. Keywords: Multimodal Analysis, PTV commercials, breaking gender stereotypes, media